express the following as the difference of two square and then factorise 25x^2+20x+3
Answers
Answered by
6
Answer:
25x² + 20x + 3 = (5x + 3)(5x + 1)
Step-by-step explanation:
25x² + 20x + 3
= 25x² + 20x + 4 - 1
= (25x² + 20x + 4) - (1)
= (5x + 2)² - (1)²
= (5x + 2 + 1)(5x + 2 - 1) ........Using a² - b² = (a+b)(a-b)
= (5x + 3)(5x + 1)
Answered by
4
Answer:
this is the answer
Step-by-step explanation:
.mark me as the brainlist
Attachments:
![](https://hi-static.z-dn.net/files/d1e/92e156833eac8e5b7b5c5899a5c9e49f.jpg)
Similar questions